2004
DOI: 10.1167/iovs.04-0064
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Intraocular Drug-Delivery System Using Crystalline Lipid Antiviral Prodrugs of Ganciclovir and Cyclic Cidofovir

Abstract: This crystalline lipid prodrug intravitreal delivery system is an effective approach to achieving sustained, therapeutic drug levels in the eye. Small microfluidized particles of HDP-P-GCV provide more rapid dissolution and higher vitreous drug levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 10 publications
1
55
0
2
Order By: Relevance
“…We have noted that it is inevitable that the RPE will more or less come with the retina when the retina is detached from the complex of RPE-Bruch's membranechoroid. 14,16 In contrast, one can get a very clean Bruch's membrane-choroid-sclera complex by completely scraping the single layer RPE off from Bruch's membrane under an ophthalmic surgical microscope. To use the Bruch's membrane-choroid-sclera complex without the RPE layer in this study meant to reduce the variation from the possible variable amount of RPE remaining on the Bruch's membrane.…”
Section: Methodsmentioning
confidence: 99%
“…We have noted that it is inevitable that the RPE will more or less come with the retina when the retina is detached from the complex of RPE-Bruch's membranechoroid. 14,16 In contrast, one can get a very clean Bruch's membrane-choroid-sclera complex by completely scraping the single layer RPE off from Bruch's membrane under an ophthalmic surgical microscope. To use the Bruch's membrane-choroid-sclera complex without the RPE layer in this study meant to reduce the variation from the possible variable amount of RPE remaining on the Bruch's membrane.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with our published data with HDP-cCDV, 100 mg per rabbit eye was the highest nontoxic dose. 9 Therefore, 100 mg/eye was chosen to do a 4-week confirmation toxicity study on 3 rabbits before the pharmacokinetic study. The right eyes were injected with 100 mg ODE-cCDV and the left eyes were injected with the equivalent volume (50 mL) of 5% dextrose.…”
Section: Preparation Of 14 C-ode-ccdvmentioning
confidence: 99%
“…7 We previously reported an intravitreal drug delivery system that conjugates a longchain alkoxyalkyl moiety to a candidate compound to render it lipophilic with low solubility in vitreous, achieving a long intravitreal half-life. 8,9 Alkoxyalkyl prodrugs penetrate cell membrane easily and are cleaved inside cells by phosphatases of the phospholipase C type, releasing the parent drug. 10 Our previous pretreatment studies demonstrated a period of 100 to 140 days of herpes simplex virus (HSV) retinitis prevention after a single intravitreal injection of alkoxyalkyl-derivatized cidofovir or GCV.…”
mentioning
confidence: 99%
See 2 more Smart Citations